Cultrural Hegemony and Reistance in Shivaraj Vijaya - Paudel, Yog Raj (English Language Teaching Perspectives, 2025)
Shivaraj Vijaya is a novel in Sanskrit language. It narrates how Muslim invaders in some parts of India controlled the territory and suppressed cultural and social freedom of native people. It also vividly depicts how the natives resist the hegemony. This research has particularly explored the ways Shivaraj Vijaya, the protagonist- a Hindu native- makes resistance strategies against the Muslim rule and succeeds in establishing counterculture hegemony. The research is based on primary and secondary data. Since it is text-based research, it has adopted inductive approach in reasoning through post-colonial perspective, forwarded mainly by Antonio Gramsci and Michael Foucault, who argue that the power of resistance exists on various sects and corners of society and prevails not in vertical but in horizontal form, empowering its effects in the micro level. Culture becomes productive force from all directions; it is not a moveable property, nor can it be stored or restored. Power and resistance are co-existing and, if handled by a courageous leader wisely and strategically, counter cultural hegemony can be a success. From this theoretical view, the findings show that the protagonist applies various plans in resisting the regime. He makes people aware of consequences of a tyrant’s control upon a territory and explains differences in social, religious and cultural freedom between the periods the country was under Hindu regime and Muslim domination. Muslim rule is juxtaposed by Shivaji’s resolution for resistance, warring strategies, constructive and caring approaches to people. He persuades the natives to be organized for resistance against Muslim cultural hegemony. This research thus highlights the pedagogical potential of Shivaraj Vijaya to foster critical thinking and awareness about resistance, leadership, and preservation of native culture. This will also enable students to understand and analyze historical and contemporary struggles against cultural hegemony as well.